The influence of metallurgical sector on Ukrainian economy - Petrushchak, Bohdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The purpose of this article is to analyze the influence of metallurgical sector on Ukrainian economy. The author tries to examine what is iron ore for Ukraine — a basis for successful economic development or resource curse, and investigate the impact of steel and iron companies on the performance of domestic stock exchange.
Keywords: Ukraina; gospodarka; sektor metalurgiczny; ruda żelaza